Forkhead box P3 gene expression and chromosomal analysis in a sample of Iraqi patients with multiple sclerosis - Aljawadi, Zainab A.; Almahdawi, Akram M.; Kashmoola, Mahmood A.N.; Abdul-Majeed, Ban A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Multiple Sclerosis disease is a demyelination process which interferes with the neuronal signal transmission, thus leading to different cognitive and physical dysfunctions like optic neuritis, motor, sensory and coordination problems. Recently many researches have been directed toward studying the relation between some genes and multiple sclerosis. Among the important genes to be studied in multiple sclerosis is the forkhead box P3 gene expression. Objectives: The aims of the present work were to study the expression of forkhead box P3 gene by real time polymerase chain reaction, and to perform chromosomal analysis on the multiple sclerosis patients peripheral blood lymphocytes. Patients and methods: A case-control study was performed using real time polymerase chain reaction technique to measure the relative expression of forkhead box P3 gene in peripheral blood leukocytes of 25 newly diagnosed untreated multiple sclerosis patients and comparing them with that of 25 apparently healthy controls, in addition to performing chromosomal analysis on multiple sclerosis patients peripheral blood lymphocytes. Results: Significant down-regulation in forkhead box P3 gene was detected in multiple sclerosis patients in comparison to controls. Chromosomal analysis that was performed for multiple sclerosis patients revealed normal results. Conclusion: Multiple sclerosis is associated with significant change in forkhead box P3 gene expression that can be measured by real time polymerase chain reaction technique. Furthermore, multiple sclerosis is not associated with gross chromosomal abnormalities.